Conodont biostratigraphy and carbon isotope chemostratigraphy of the Furongian (Cambrian) and Lower Ordovician in the Zhejiang Province, southeast China - Yan, Guanzhou; Calner, Mikael ; 0000-0003-1096-3153; Jahangir, Hadi; Wu, Rongchang (Newsletters on Stratigraphy, 2025)
This paper presents an integrated conodont biostratigraphy and carbon isotope chemostratigraphy for the Cambrian-Ordovician transition in western Zhejiang, southeast China. Eight conodont zones can be recognized, in ascending order the Westergaardodina cf. calix-Prooneotodus rotundatus, Proconodontus, Eoconodontus, Cordylodus proavus, Cordylodus intermedius, Cordylodus lindstromi, Cordylodus angulatus, and the Rossodus manitouensis zones. These zones help to stratigraphically constrain six δ13Ccarb excursions and shifts that are documented from the succession and that are herein identified as the falling limb of the SPICE, chemostratigraphic tie-point N1, chemostratigraphic tie-point N2, Hellnmaria-Red Tops Boundary (HERB) Event or the conceptually synonymous Top of Cambrian Excursion (TOCE), Cordylodus proavus spike (CPS), and chemostratigraphic tie-point C3, thus providing an improved regional and global bio-chem ostratigraphic correlation of the studied strata.
Publisher Copyright: © 2025, Schweizerbart Science Publishers. All rights reserved.
Keywords: carbon isotope stratigraphy; conodont biostratigraphy; HERB/TOCE; SPICE; upper Cambrian